Rab27a and Rab27b control different steps of the exosome secretion pathway - Ostrowski, M. (2010)
Exosomes are secreted membrane vesicles that share structural and biochemical characteristics with intraluminal vesicles of multivesicular endosomes (MVEs). Exosomes could be involved in intercellular communication and in the pathogenesis of infectious and degenerative diseases. The molecular mechanisms of exosome biogenesis and secretion are, however, poorly understood. Using an RNA interference (RNAi) screen, we identified five Rab GTPases that promote exosome secretion in HeLa cells. Among these, Rab27a and Rab27b were found to function in MVE docking at the plasma membrane. The size of MVEs was strongly increased by Rab27a silencing, whereas MVEs were redistributed towards the perinuclear region upon Rab27b silencing. Thus, the two Rab27 isoforms have different roles in the exosomal pathway. In addition, silencing two known Rab27 effectors, Slp4 (also known as SYTL4, synaptotagmin-like 4) and Slac2b (also known as EXPH5, exophilin 5), inhibited exosome secretion and phenocopied silencing of Rab27a and Rab27b, respectively. Our results therefore strengthen the link between MVEs and exosomes, and introduce ways of manipulating exosome secretion in vivo.